Analisis Komparatif Krisis Likuiditas Sektoral pada Palestine Exchange (PEX) dan Bursa Efek Indonesia (BEI) - Hasbih Soleh Suryadi; Maryam Batubara (Masyarakat Ekonomi Syariah Bogor, 2026)
This study aims to comparatively analyze the impact of monetary structures and Islamic financial architecture on the stability of banking sectors listed on capital markets, using the Palestine Exchange (PEX) and the Indonesia Stock Exchange (IDX) as case studies. Employing a political-economy approach and structural analysis, the study examines how the absence of monetary sovereignty triggered the anomaly known as